A novel type cold mix pavement material made with calcium-alginate and aggregates. (1st March 2019) - Alenezi, Thamer; Norambuena-Contreras, José; Dawson, Andrew; Garcia, Alvaro
Abstract: This paper has been prepared in the frame of a research focused on the development of Cold Mix pavement materials made with calcium-alginate Capsules (CMC) instead of with just bitumen emulsion, as it is normally made. The initial objective was to remove most of the water in cold mix asphalt by encapsulating bitumen droplets. The encapsulation method allowed the preparation of polynuclear capsules with bitumen emulsion encapsulated, which membrane was made of calcium-alginate. Capsules were mixed with aggregates at the ambient temperature. During mixing, the capsules containing bitumen emulsion would break, release their content and coat the aggregates. To study CMC, an extensive experimental programme has been carried out to evaluate the effect of compaction energy, cement content, curing time and binder type on the mechanical properties of CMC. It was found that CMC test samples increased their Marshall stability linearly with the increase of the compaction energy. Test samples could be demoulded immediately after compaction. Furthermore, the Marshall stability of CMC increased with the curing time, and the general strength improved with the increasing amount of capsules in the mixture. It was found that the bitumen in CMC did not have an important role on the strength of the pavement material, which came mainly from the alginate in the capsules. In short, cold mix pavement materials made with calcium-alginate (Ca-alginate) capsules is a novel material for pavements that has shown potential to be an alternative for conventional cold mix asphalt made with bitumen emulsion. Highlights: Alginate and Portland cement have been tested as a new binder for pavements. The materials could be mixed and compacted at the ambient temperature. The mechanical stability of the new pavement material was evaluated. The strength of the material was equivalent to that of a hot mix asphalt after 24 h curing. The new material could be loaded by traffic after less than 24 h curing.